Inventory of Glaciers in Mongolia, Derived from Landsat Imagery from 1989 to 2011. Issue 4 (14th May 2015) - Kamp, Ulrich; Pan, Caleb G.
ABSTRACT: Glaciers in the Altai Mountains of Mongolia provide an estimated 11% of the total water resources within the country. Yet, their number and area in inconsistent. Using satellite imagery acquired from Landsat 4, 5, and 7, and SRTM digital elevation model (DEM) data, we present here an intuitive, robust, and inexpensive methodology to map the exposed ice of glaciers in the Altai Mountains for the period 1989 to 2011. The total glacierized area was 515 km 2 in 1989/1991, 428 km 2 in 1998/2001, and 372 km 2 in 2010/2011; it decreased by 17% from 1989/1991 to 1998/2001, 13% from 1998/2001 to 2010/2011, and 28% for the entire period 1989/1991 to 2010/2011. In analyzing a sub‐sample of 260 glaciers, 6% advanced, 11% were stable, and 83% receded from 1989 to 2011. The glacier dataset is available to the public free of charge at the Global Land Ice Measurements from Space (GLIMS) website.